Peran Pola Asuh Orang Tua Terhadap Keberhasilan Memimpin - Juwinner Dedy Kasingku; Claudia Meybi Tampanguma; Edwin Melky Lumingkewas (Jurnal Ilmiah Wahana Pendidikan, 2023)
Each parent in the family has their own way of raising children. Parenting from people who know plays an important role, especially in helping form a child's abilities. The purpose of this research is to make readers understand more, especially the role of parents, parenting, and successful leadership. The method used in this research is a qualitative method with a combination of library research approaches coupled with various sources from the internet. This study discusses the role of parents, parenting styles, types of parenting styles, leaders and leadership, leadership styles, leadership success, and the relationship between success in leadership and parenting styles. The three types of parenting are authoritarian, democratic, and permissive. The leadership style is autocratic, laissez-faire, and democratic. In a variety of parenting styles, not all of them can give good results in shaping children's attitudes and abilities. Likewise, with leadership styles, not all can show success in leading. The results of this study indicate that one's success in leading cannot be separated from the role of parents regarding the ability of children resulting from the application of parenting patterns. Everything that is good and successful comes from democratic parenting and democratic leadership styles. The relationship can be seen in several attitudes, namely good communication, cooperation, making decisions, and being responsible